Cover Image. (12th December 2019) - Sgammato, Roberta; Herrebout, Wouter; Johannessen, Christian
Abstract : The cover image is based on the Research Article Resonance Raman Optical Activity of the Imidazole‐Myoglobin complex: Titrating enhancement by Roberta Sgammato et al., https://doi.org/10.1002/jrs.5735 .